Envisioning Critical Pedagogy in Liberian Higher Education: A Conceptual Framework for Civic and Democratic Engagement - Kennedy, Gabriel M. (Critical Education, 2026)
Liberia's higher education system, shaped by colonial legacies, neoliberal reforms, and fragile democratic institutions, functions less as a site of civic empowerment than as a mechanism that reproduces inequality and constrains democratic agency. Rather than operating as a neutral public good, education in this context is embedded within political-economic structures that reinforce rather than challenge elite dominance. Against this backdrop, the paper argues that critical pedagogy, emphasizing dialogic learning, critical thinking, and civic engagement, offers a framework for reimagining higher education as a space of democratic renewal. Adopting a conceptual literature review with an argumentative orientation, the study synthesizes international and African philosophical traditions of critical pedagogy to assess their relevance for post-conflict Liberia. It underscores the risks of uncritical borrowing, which can reinforce epistemic dependency and alienate students from indigenous cultural frameworks. To address these risks, the paper proposes the Liberian Critical Praxis/Dialogic approach, a localized framework built on three interrelated pillars: dialogic instruction rooted in cultural practices such as the palava hut, integration of indigenous knowledge into curricula, and ethical reasoning, including critical media literacy, anchored in communal responsibility. The paper concludes that reform must be gradual, context-sensitive, and culturally grounded. By situating Indigenous perspectives alongside international theory, the Liberian Critical Praxis/Dialogic approach contributes to debates on decolonizing higher education and demonstrates how post-conflict universities can foster democratic participation and civic resilience.